PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN LITERASI SAINS SISWA - Dwiyanti, Sekar; A.A. Musyaffa; Nurhasanah, Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted to address the low level of students’ scientific literacy in IPAS learning, particularly on biodiversity topics. This issue was evident in students’ limited ability to understand scientific concepts, relate scientific knowledge to their surrounding environment, and explain as well as draw simple conclusions from scientific information. The study aimed to investigate the implementation of the Project Based Learning (PjBL) model in improving students’ scientific literacy, identify challenges encountered during project-based learning, and describe strategies to overcome these challenges. This research employed a Classroom Action Research (CAR) design conducted in two cycles consisting of planning, action, observation, and reflection. The participants were fourth-grade students of MI Al-Munawwarah, Jambi City. Data were collected through observation, interviews, documentation, and scientific literacy questionnaires. The results indicated that the application of the PjBL model significantly improved students’ scientific literacy, increasing from 16.7% in the pre-cycle to 58.3% in Cycle I and further to 87.5% in Cycle II. Therefore, Project Based Learning (PjBL) is effective in enhancing students’ scientific literacy on biodiversity in IPAS learning.